2009
DOI: 10.1007/s11099-009-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapidly imposed water deficit on photosynthetic parameters of three C<sub>4</sub> grasses

Abstract: Water deficit, when rapidly imposed on three C 4 grasses of the different metabolic subtypes, Paspalum dilatatum Poiret (NADP-malic enzyme), Cynodon dactylon (L.) Pers (NAD-malic enzyme) and Zoysia japonica Steudel (phosphoenolpyruvate carboxykinase), caused decreases in photosynthetic rates, in the quantum yield of PS II and photochemical quenching, and in the activities of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) and phosphoenolpyruvate carboxylase (PEPC). The results provide evidence for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Plants that experience drought conditions often appear serious physiological and biochemical dysfunctions, including: reduction in turgor, growth, photosynthetic rate, and stomatal conductance, as well as damage to various cellular components [2,3]. Plants utilize various mechanisms to adapt to and withstand drought conditions [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants that experience drought conditions often appear serious physiological and biochemical dysfunctions, including: reduction in turgor, growth, photosynthetic rate, and stomatal conductance, as well as damage to various cellular components [2,3]. Plants utilize various mechanisms to adapt to and withstand drought conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…In turfgrass management, drought constitutes a major factor limiting grass growth. Some researchers have studied the morphological and physiological responses of zoysiagrass to drought conditions [3,31–33]. However, to our knowledge, few attempts have been made to study the alleviation of such negative effects to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“… Flexas and Medrano (2002) suggested that, in C 3 plants, Rubisco capacity was of little importance in the drought-induced limitation of photosynthesis, whilst decreased capacity for RuBP regeneration—possibly as a result of decreased ATP synthesis or impaired Calvin cycle enzyme activities ( Lawlor, 2002 )—would constitute a major metabolic limitation. However, decreased activity and/or quantity of Rubisco has been observed in several different C 3 and C 4 species exposed to water deficit ( Majumdar et al , 1991 ; Du et al , 1996 ; Lal and Edwards, 1996 ; Parry et al , 2002 ; Tezara et al , 2002 ; Bota et al , 2004 ; Marques da Silva and Arrabaça, 2004 ; Carmo-Silva et al , 2007 ; Soares-Cordeiro et al , 2009) .…”
Section: Introductionmentioning
confidence: 99%
“…In the process of plant growth, organisms are subjected to various adverse environmental stresses, among which drought is one of the most common abiotic stresses. The effects of drought stress on plants are mainly reflected in the effects on cell activity and organ and tissue function [ 1 , 2 ]. A decrease in the water content will result in the inhibition of photosynthesis, the slow growth of plants, and influence of the biomass or yield [ 3 ].…”
Section: Introductionmentioning
confidence: 99%